From peacetime to war: a path analysis of the factors that predict performance among police and military commanders in collaborative crisis response - Mattingsdal, Jostein; Aandal, Jan; Johnsen, Bjørn Helge; Espevik, Roar (Frontiers in Psychology, 2023)
One hundred and thirty eight high-ranking police and military commanders participated in a simulation involving a scenario that escalated from peace to war. A key question was whether the theoretical framework described by Albert Bandura`s (1986) social cognitive theory could predict organizational performance in dynamic and ambiguous hybrid warfare contexts. The participants were assigned to three types of dyads (N = 69); all-police (n = 20), all-military (n = 27), and mixed police-military (n = 22). The study investigated two fixed social cognitive factors (dyad composition and past performance in peacetime) and two relatively pliable factors (collective self-efficacy and persistence). A model was composed accounting for 54% of the variance in wartime performance (R² = .54). Path analysis showed direct effects of persistence (β = -.33) and peacetime performance (β = .45) on actual performance in wartime.Direct effects also showed how persistence was predicted by dyad composition (β = -.24) and peacetime performance (β = -.50). Indirect effects indicated how persistence mediated the effects of peacetime performance (β = .17) and dyad composition (β = .08) on actual performance in wartime. The results illustrate the extent to which the self-regulatory mechanisms described by SCT can predict the decision outcomes of police and military commanders in settings involving collaborative crisis response. Policy implications are discussed, and recommendations are made for further study.